PEMIKIRAN PENDIDIKAN ISLAM IBN MISKAWAIH - Hadis Purba (State Islamic University North Sumatra, 2009)
Abstract: Eductional Thought of Ibn Miskawah. In the rank of great classical Muslim thinkers we have Ibn Miskawaih, mostly popular as a philosopher specializing in moral philosophy. His writings have attracted numerous scholars and initiated lively debates among students. Our present writer makes a new thrust into the thought of Ibn Miskawayh, arguing that in fact he also advanced great educational thought in his magnum opus, Tahzîb al-Akhlâq. In addition to outlining his thoughts, the writer also attempt to explain the relevance of these thoughts to present day education.Kata Kunci: Pendidikan, konsep manusia, dan akhlak